2011
DOI: 10.1029/2010wr010213
|View full text |Cite
|
Sign up to set email alerts
|

Probing the integration of land use and watershed planning in a shifting governance regime

Abstract: [1] Effective governance that contributes to the integration of water management and land use planning is essential for successful protection of drinking water sources and, ultimately, provision of safe drinking water. In many jurisdictions, land use planning and watershed management occur on separate tracks. This article examines the prospects for integration of these two critical processes. A multicase study approach is used, focusing on the specific objective of protection of drinking water sources. Experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 51 publications
2
17
0
7
Order By: Relevance
“…Many researchers have observed that failure to provide safe drinking water is not (solely) a result of a lack of scientific understanding, but also due to institutional and organizational failures such as inadequate financial resources, weak standards, failure to implement or enforce standards, lack of skilled staff, rivalries among agencies and insufficient political will (see e.g. de Loë and Kruetzwiser 2005;Ivey et al 2006;Plummer et al 2011). These various factors are often referred to by the general term "governance" -the laws, rules, regulations, policies, practices and institutions related to the management of water.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have observed that failure to provide safe drinking water is not (solely) a result of a lack of scientific understanding, but also due to institutional and organizational failures such as inadequate financial resources, weak standards, failure to implement or enforce standards, lack of skilled staff, rivalries among agencies and insufficient political will (see e.g. de Loë and Kruetzwiser 2005;Ivey et al 2006;Plummer et al 2011). These various factors are often referred to by the general term "governance" -the laws, rules, regulations, policies, practices and institutions related to the management of water.…”
Section: Introductionmentioning
confidence: 99%
“…Shifting from a recent history of funding cutbacks for monitoring and evaluation of water quality, the Walkerton crisis provided the impetus for new legislation and a stronger regulatory framework to not only monitor water quality, but also for better integration between land use planning and watershed management [66,67].…”
Section: Democratised Performancementioning
confidence: 99%
“…In real terms, this monopoly means that they have the power to define, develop and implement policies regulating land use. However, their involvement in the planning process for water resource management has fallen short of expectations, since they still give priority to their own political interests, with decisions still heavily influenced by local economic and social issues [20,21]. As a result, land-use planning based around water resource management principles may not fully achieve its potential benefits, due to incompatibility between the goals of river basin management and the political interests of the local governments.…”
Section: Introductionmentioning
confidence: 96%